Do Small Local Governments Fare Well? A Survey of Villages in New York. Issue 1 (January 2020) - Zhang, Pengju; Holzer, Marc
Public administration studies have not adequately discussed governance challenges for small local governments. Given that more than 10% of villages have, unprecedentedly, voted on dissolution in New York over the past 10 years, this article exclusively and comprehensively investigates how well villages are faring in New York. Using a representative survey of village governments, coupled with a rich secondary data set, it finds institutional and political tensions between villages and their underlying town(s). It also suggests intergovernmental fiscal factors have threatened the organizational and fiscal health of some village governments. In addition, villages have extensively established service-sharing mechanisms with town(s) to mitigate fiscal stress. The majority of village officials remain skeptical about dissolution as an effective approach to cost savings.